1953
DOI: 10.1152/ajplegacy.1953.173.2.275
|View full text |Cite
|
Sign up to set email alerts
|

Size of the Largest Arterio-Venous Vessels in Various Organs

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1956
1956
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Thus there was no arterio-venous or porto-venous anastomoses large enough to allow microspheres (15 + 5,um diameter) to pass through them. This confirms other evidence that there are no shunt vessels in the normal liver (Gordon, Flasher & Drury, 1953;Ohlsson, Rutherford, Boitnott, Haalebos & Zuidema, 1970).…”
Section: Discussionsupporting
confidence: 87%
“…Thus there was no arterio-venous or porto-venous anastomoses large enough to allow microspheres (15 + 5,um diameter) to pass through them. This confirms other evidence that there are no shunt vessels in the normal liver (Gordon, Flasher & Drury, 1953;Ohlsson, Rutherford, Boitnott, Haalebos & Zuidema, 1970).…”
Section: Discussionsupporting
confidence: 87%
“…There seems to be good evidence that in the resting basal state not all pulmonary capillaries are functional at any given moment (16). A fair amount of evidence has also accumulated that pulmonary arteriovenous anastomoses exist in mammalian (16)(17)(18)(19) 3. As a result of the increased pulmonary blood flow there may occur increased pressure distention of the pulmonary vascular bed (20); this may conceivably be followed by a progressive decrease in intrinsic or neurogenically controlled vascular "tone" as a compensatory phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Wearn, Ernstene, Bromer, Barr, German & Zschiesche (1934) showed that in the anaesthetized cat not all the subpleural capillary bed was open at any one time so that new channels S. D. CARLILL AND HELEN N. DUKE would probably be available. It is also possible that arterio-venous anastomoses are present which might open up (Gordon, Flasher & Drury, 1953;Prinzmetal, Ornitz, Simkin & Bergman, 1948;Pritchard, Daniel & Ardian, 1954).…”
Section: Discussionmentioning
confidence: 99%